Globalization, income distribution and sustainable development : a theoretical and empirical investigation - Das, Ramesh Chandra (Emerald Publishing Limited, 2022)
Most countries in the world today have entered an advanced phase of globalization with the objective of increasing growth of output and employment. With the evidence suggesting that this has been the case at a general level incorporated with a good sign of reducing income gap at the global level and an acceptable trend towards a global village, some inequalities across different groups of economies have been increasing in hand with the resultant increase in the aggregate pollution levels. The combined effects of these two negative impacts gives rise to the problem of maintaining sustainable development. Globalization, Income Distribution and Sustainable Development: A theoretical and empirical investigation addresses these feasibility issues of globalization, focusing on the impact of globalization on income distribution in a wider perspective and exploring the impact of globalization on sustainable development in a range of countries across the globe. With the help of new theories and the latest data, Globalization, Income Distribution and Sustainable Development asks the question: Are we eyeing for a better future?